Chemical and physicochemical profiles of essential oil from Piper betel (L.) cultivated in different regions of Vietnam : Chemical and physicochemical profiles of essential oil from Piper betel (L.) cultivated in different regions of Vietnam - Hoang, Son; Le, Thanh; Nguyen, Duong (Comunicata Scientiae, 2025)
This study aimed to investigate the variation of essential oils from Piper betel cultivated in three different geographic regions of Vietnam (Hoc Mon, Tien Giang, and Dak Lak). The extraction of essential oil was conducted by hydro-distillation for 3 h using a Clevenger-type apparatus. GC-MS was employed for the analysis of obtained essential oil. Physicochemical parameters were determined as per standard test methods. GC-MS revealed the highest amount of chavibetol present in all three essential oils of Piper betel cultivated in three different geographic regions of Vietnam: Hoc Mon (49.077%), Tien Giang (39.982%) and Dak Lak (34.888%). In contrast to the absence of Cadinene in both Hoc Mon and Tien Giang essential oils, there was remarkably an extremely high content of Cadinene present in Dak Lak essential oil, accounting for approximately 49% of the total constituents of essential oil. α-Cadinene was recorded to be the highest quantity (19.826%), followed by γ-Cadinene (15.470%) and δ-Cadinene (13.369%). Nature variation in different geographic regions of Vietnam (Hoc Mon, Tien Giang, and Dak Lak) plays a key role in the diversification of essential oil composition in Piper betel.